Analisis Pengelolaan Usaha Dalam Meningkatkan Pendapatan Sarang Burung Walet Di Desa Sungai Aur Kecamatan Kumpeh Ilir Kabupaten Muaro Jambi Provinsi Jambi - Bambang Heriyanto; Hansen Rusliani; Hareastoma Hareastoma (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research discusses the analysis of business management in increasing income from swallow nests in Sungai Aur Village, Kumpeh Ilir District, Muaro Jambi Regency, Jambi Province. The aim of this research is to find out the management of the swallow's nest business, to find out the obstacles faced in managing the swallow's nest business and to find out the efforts made in managing the swallow's nest business. This study used qualitative research methods. Data collection techniques use observation, interviews and documentation methods. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this research show that the management of the swallow's nest business is not good because there are several indicators or functions in business management that have not been achieved by entrepreneurs, business management takes the form of planning, organizing, mobilizing and controlling. The obstacles in managing the swallow's nest business are rodent pests, owls, location and seasonality. Efforts made in managing the swallow's nest business are by providing poison or pest medicine.